2021
DOI: 10.1155/2021/6662247
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology Strategy to Investigate the Pharmacological Mechanism of Siwu Decoction on Primary Dysmenorrhea and Molecular Docking Verification

Abstract: Objective. To study the pharmacological mechanisms of Siwu decoction (SWD) on primary dysmenorrhea (PDM) and verify with molecular docking. Methods. The  Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP) was utilized to acquire the active compounds and their corresponding target genes. The GeneCards database was utilized in the search for target genes that were associated with PDM. The intersection genes from the active target genes of SWD and those associated with PDM re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Prostaglandins may cause ischemia by acting on the myometrium and blood vessels of the uterus to promote contraction of uterine arteries and smooth muscles, thus manifesting the following symptoms: abdominal cramp, nausea, and vomiting. In TCM, it is believed that PD is caused by blood stasis [ 17 , 18 ]. Similar to previous studies, we also demonstrated that EA could reduce the pain experienced by all PD participants, regardless of the TCM diagnoses in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandins may cause ischemia by acting on the myometrium and blood vessels of the uterus to promote contraction of uterine arteries and smooth muscles, thus manifesting the following symptoms: abdominal cramp, nausea, and vomiting. In TCM, it is believed that PD is caused by blood stasis [ 17 , 18 ]. Similar to previous studies, we also demonstrated that EA could reduce the pain experienced by all PD participants, regardless of the TCM diagnoses in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The structures of the target proteins were obtained from the RCSB PDB database ( https://www.rcsb.org/ ), and the compounds were obtained from the PubChem database ( https://pubchem.ncbi.nlm.nih.gov/ ). Molecular docking simulations of target proteins with their corresponding compounds were performed using AutoDockTool 1.5.6 and AutoDock Vina software [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%